Chapter 9: Malnutrition's new frontier: The challenge of obesity [Nourishing Millions] - Hodge, Judith; Verstraeten, Roosmarijn; Ochoa-Avilés, Angélica (2016)
OVERWEIGHT AND OBESITY prevalence has increased substantially over the past decades, affecting 2.1 billion people worldwide and causing 3.4 million deaths globally.1 Currently, 42 million children are overweight or obese—the result of a staggering 47.1 percent rise in prevalence between 1980 and 2013.2 No longer exclusive to affluent societies, obesity has reached alarmingly high levels in many low- and middle-income countries (LMICs).3 In fact, the number of individuals who are overweight or obese (1.9 billion) has now surpassed the 794 million people who do not get enough calories.4 Nearly half of all overweight children under 5 years of age now live in Asia, and a further 25 percent are found in Africa.